Chemical composition of lettuce following root-application of osmolytes in hydroponic cultivation - Uusitupa, Jenni; Edelmann, Minnamari; Jokinen, Kari; Simpura, Ilkka; Shapiguzov, Alexey; Mäkelä, Pirjo S.A. (Elsevier, 2026)
Hydroponically produced lettuce (Lactuca sativa L.,) naturally accumulates high amounts of nitrate in its leaves, and this compound is harmful for human health. Osmolytes affect the osmotic potential of plant cells and can potentially reduce the accumulation of nitrate. The potential of osmolytes mannitol and glycerol was compared to glycinebetaine —which is known to decrease the nitrate content of lettuce— in two hydroponic experiments. Plant samples were collected at various time points and analyzed for minerals, free- and hydrolyzed amino acids, soluble sugars, osmolality, and nitrate. All three osmolytes reduced the nitrate content in lettuce leaves and increased the contents of dry matter, soluble sugars, and some amino acids. The effect of mannitol and glycerol on lettuce nitrate content and quality were similar to those induced by glycinebetaine. Thus, the quality of hydroponically grown lettuce can be controlled with diverse types of root-applied osmolytes.
Keywords: leafy vegetables; NFT-cultivation; sugars; amino acids; nitrate; minerals